Britain in China - Bickers, Robert (Studies in Imperialism, 2017)
This is a study of Britain's presence in China both at its peak, and during its inter-war dissolution in the face of assertive Chinese nationalism and declining British diplomatic support. Using archival materials from China and records in Britain and the United States, the author paints a portrait of the traders, missionaries, businessmen, diplomats and settlers who constituted "Britain-in-China", challenging our understanding of British imperialism there. Bickers argues that the British presence in China was dominated by urban settlers whose primary allegiance lay not with any grand imperial design, but with their own communities and precarious livelihoods. This brought them into conflict not only with the Chinese population, but with the British imperial government. The book also analyzes the formation and maintenance of settler identities, and then investigates how the British state and its allies brought an end to the reign of freelance, settler imperialism on the China coast. At the same time, other British sectors, missionary and business, renegotiated their own relationship with their Chinese markets and the Chinese state and distanced themselves from the settler British.